Exploration of Microbial Diversity and Community Structure of Lonar Lake: The Only Hypersaline Meteorite Crater Lake within Basalt Rock - Paul, Dhiraj; Kumbhare, Shreyas V.; Mhatre, Snehit S.; Chowdhury, Somak P.; Shetty, Sudarshan A.; Marathe, Nachiket P.; Bhute, Shrikant; Shouche, Yogesh S. (Frontiers in Microbiology, 2016)
Lonar Lake is a hypersaline and hyperalkaline soda lake and the only meteorite impact crater in the world situated in basalt rocks. Although culture-dependent studies have been reported, a comprehensive understanding of microbial community composition and structure in Lonar Lake remains elusive. In the present study, microbial community structure associated with Lonar Lake sediment and water samples was investigated using high-throughput sequencing. Microbial diversity analysis revealed the existence of diverse, yet largely consistent communities. Proteobacteria (30%), Actinobacteria (24%), Firmicutes (11%), and Cyanobacteria (5%) predominated in the sequencing survey, whereas Bacteroidetes (1.12%), BD1-5 (0.5%), Nitrospirae (0.41%), and Verrucomicrobia (0.28%) were detected in relatively minor abundances in the Lonar Lake ecosystem. Within the Proteobacteria phylum, the Gammaproteobacteria represented the most abundantly detected class (21–47%) within sediment samples, but only a minor population in the water samples. Proteobacteria and Firmicutes were found at significantly higher abundance (p ≥ 0.05) in sediment samples, whereas members of Actinobacteria, Candidate division TM7 and Cyanobacteria (p ≥ 0.05) were significantly abundant in water samples. Compared to the microbial communities of other hypersaline soda lakes, those of Lonar Lake formed a distinct cluster, suggesting a different microbial community composition and structure. Here we report for the first time, the difference in composition of indigenous microbial communities between the sediment and water samples of Lonar Lake. An improved census of microbial community structure in this Lake ecosystem provides a foundation for exploring microbial biogeochemical cycling and microbial function in hypersaline lake environments.